Communication Technologies and Specialised Communication Protocols for Ensuring Cybersecurity of the Internet of Things (Law and Safety, 2025)
Internet of Things devices are characterised by limited resources in terms of power, processing, memory and bandwidth. As a result, traditional protocols relating to network operations and security cannot be implemented in their current form in the specific environment of the Internet of Things.Standardisation is necessary for the organisation of IoT interaction, because without established regulations, precise instructions and global standards, the industry will eventually face serious compatibility and security issues. In addition, many IoT devices process sensitive data that they can autonomously collect and distribute to other devices or the network. There is a need for stronger data protection measures and stricter controls for IoT devices that authenticate and interact on the network. Protecting IoT devices and communication protocols has become a priority in our increasingly connected world.It is noted that the analysis of the security of IoT communication technologies using specialised communication protocols across networks with different topologies, communication ranges and bandwidths is a pressing issue, as the number of security and privacy breaches in the IoT ecosystem is growing, which is constantly expanding in various sectors of the economy and human life with the introduction of billions of heterogeneous smart devices. In addition, many Internet of Things networks cover a wide range of communication protocols, some of which may not have reliable security features, making them vulnerable to attacks.The term “communication technology” is used to define communication protocols at each level of the Internet of Things platform architecture. In an effort to provide a better understanding of the architecture and use of Internet of Things technologies, the taxonomy presented in the article facilitates the effective separation of relevant Internet of Things technologies into channel-level protocols, network encapsulation protocols, and routing protocols according to their standards.The study may encourage scientists and professionals to develop new and more effective network protocols based on the current gaps and shortcomings discussed in the article.
Keywords: Internet of Things; Internet of Things architecture; Internet of Things security; Internet of Things security protocols; Internet of Things communication protocols; network protocols; cellular communication.